2008
DOI: 10.1161/circulationaha.107.728022
|View full text |Cite
|
Sign up to set email alerts
|

Complementary Roles for Biomarkers of Biomechanical Strain ST2 and N-Terminal Prohormone B-Type Natriuretic Peptide in Patients With ST-Elevation Myocardial Infarction

Abstract: Background-ST2 is a member of the interleukin-1 receptor family with a soluble form that is markedly upregulated on application of biomechanical strain to cardiac myocytes. Circulating ST2 levels are elevated in the setting of acute myocardial infarction, but the predictive value of ST2 independent of traditional clinical factors and of an established biomarker of biomechanical strain, N-terminal prohormone B-type natriuretic peptide (NT-proBNP), has not been established. Methods and Results-We measured ST2 at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
252
1
24

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 300 publications
(289 citation statements)
references
References 24 publications
12
252
1
24
Order By: Relevance
“…Data from a retrospective study by Hirsch et al showed an association between aortic stiffness and LV end‐systolic volume in patients with chronic infarcts 8. A rise in NT‐proBNP concentration is a sensitive indicator of increasing myocardial wall stress and a strong predictor of outcome after acute STEMI 6, 22. Our study group has recently shown an association between high aortic PWV and NT‐proBNP levels in the subacute and chronic phase after STEMI 2, 3.…”
Section: Discussionmentioning
confidence: 50%
“…Data from a retrospective study by Hirsch et al showed an association between aortic stiffness and LV end‐systolic volume in patients with chronic infarcts 8. A rise in NT‐proBNP concentration is a sensitive indicator of increasing myocardial wall stress and a strong predictor of outcome after acute STEMI 6, 22. Our study group has recently shown an association between high aortic PWV and NT‐proBNP levels in the subacute and chronic phase after STEMI 2, 3.…”
Section: Discussionmentioning
confidence: 50%
“…Circulating sST2 was previously identified as a prognostic marker in heart failure and myocardial infarction 7, 8, 9, 24. Together with other cardiac biomarkers such as troponin25 and B‐type natriuretic peptide (BNP),26, 27 our data highlight overlapping injury responses that occur following both cerebrovascular and cardiovascular injury.…”
Section: Discussionmentioning
confidence: 56%
“…Previous studies have identified sST2 as a prognostic biomarker in cardiovascular disease 7, 8, 9. In order to exclude the possibility that the association between sST2 and outcome was related to underlying cardiovascular disease, we developed sequential multivariable models that included cardiovascular disease risk factors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The involvement of sST2 has been observed in a variety of pathological conditions characterized by: (1) intravascular inflammation [145,[148][149][150][151] (i.e. myocardial infarction [152][153][154], atherosclerotic vascular disease [155], sepsis and trauma [149,150]); and (2) an imbalance of Th1/Th2 immune response [141,156,157] (i.e. asthma and other allergic conditions [145,148,158,159]), both of which are also observed in patients with preeclampsia [23,25,132,160,161].…”
Section: Introductionmentioning
confidence: 99%